Users' Perception of Violence and Conflicts With Professionals in Primary Care Centers Before and During COVID-19. A Qualitative Study - Pina, David; López-Ros, Paloma; Luna-Maldonado, Aurelio; Luna Ruiz-Caballero, Aurelio; Llor-Esteban, Bartolomé; Ruiz-Hernández, Jose Antonio; García-Jiménez, Jesús Javier; Puente-López, Esteban; Martínez-Jarreta, Begoña (Frontiers in Public Health, 2021)
Background: Workplace violence is a social problem of special interest in both intervention and research. Among the sectors that most perceive this type of violence, health care professionals stand out. The most common type of violence for this professional group is the one perpetrated by the users or patients themselves. It has been reported that one out of every four acts of violence in the workplace occurs in the healthcare setting. Within the health sector, the Mental Health, Emergency and Primary Care services have been widely reported as being among the most vulnerable, with Primary Care being the least addressed of the three. Objective: The aim of this study is to examine, from the users’ perspective, those aspects derived from the organization, the professional or the user of Primary Care that cause violent situations and how they think these could be avoided. Method: The sample consisted of 80 users of the Primary Care services of the Health Service of Murcia. For data collection, a qualitative study was conducted through 10 focus groups and a subsequent thematic analysis of the data. Results: The results have allowed us to identify that, from an organizational point of view, the uncertainty in waiting times, the need to adapt the telematic or telephone appointment to the different types of users, or the management of emergencies in Primary Care are the aspects that cause most conflicts between users and professionals. As for the professionals, users point out that the staff is perceived as distant and sometimes does not provide enough information on the health status of users. From the users' perspective, the existence of a demanding/aggressive user profile is recognized, who makes instrumental use of violence to achieve privileges as opposed to normative users. Conclusion: The identification of sources of conflict and the assessment and contribution of users on possible ways of improvement can serve as a basis for the design of prevention and intervention plans to improve the work environment in Primary Care centers.